1982
DOI: 10.1007/bf03007945
|View full text |Cite
|
Sign up to set email alerts
|

Lorazepam and diazepam as adjuncts to epidural anaesthesia for caesarean section

Abstract: Lorazepam 0.05 mg-kg -1 and diazepam 0.1 mg-kg -t administered intravenously were compared as sedatives for 42 patients undergoing Caesarean Section under epidural anaesthesia. After receivin~ the drug, 15 per cent of the diazepam patients and 32 per cent of the lorazepam patients were still agitated. Ten per cent of the diazepam patients and 36 per cent of the lorazepam patients had severe symptoms of delirium. These included hallucinations, confusion, agitation, restlcssness, inappropriate weeping and repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Fourthly, childbirth often involves the use of analgesia. The effect of analgesia on birth memories is unclear but some studies have shown it can cause varying degrees of amnesia [43-45] and Briddon et al . [7] suggest that analgesia with greater consciousness-affecting (rather than pain-affecting) properties may be associated with more disorganised memories of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, childbirth often involves the use of analgesia. The effect of analgesia on birth memories is unclear but some studies have shown it can cause varying degrees of amnesia [43-45] and Briddon et al . [7] suggest that analgesia with greater consciousness-affecting (rather than pain-affecting) properties may be associated with more disorganised memories of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Ong et al . reported delirium, hallucination, confusion and agitation following intravenous administration of lorazepam (0.05 mg.kg −1 ), in patients undergoing Caesarean section under epidural anaesthesia [2]. However, in the present case, the patient was elderly and received oral lorazepam that caused an adverse event that led to the postponement of surgery.…”
mentioning
confidence: 73%